1997
DOI: 10.1086/310599
|View full text |Cite
|
Sign up to set email alerts
|

Time Delay of QSO 0957+561 and Cosmological Implications

Abstract: We obtain the time delay between the arrival time of the A and B images of the QSO 0957+561. The results of applying two di erent methods (the discrete cross{correlation function and the dispersion estimation technique) to the observed light curves of the A and B images are presented. The adopted value (time delay) is of BA = 424 3 days (1). We have used this time delay as well as a recent measurement of the 1D velocity dispersion of the main lensing galaxy (gal) to estimate H 0. Two H 0 = H 0 (BA ; gal) relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 13 publications
3
37
0
Order By: Relevance
“…The A component w as active (Kundic et al 1995), and also, we have not found evidences of strong microlensing in the r R comparison (Oscoz et al 1997, Goicoechea et al 1998. A similar result (417 3 days; 2 con dence level) has been derived by Kundic et al (1997).…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…The A component w as active (Kundic et al 1995), and also, we have not found evidences of strong microlensing in the r R comparison (Oscoz et al 1997, Goicoechea et al 1998. A similar result (417 3 days; 2 con dence level) has been derived by Kundic et al (1997).…”
Section: Introductionsupporting
confidence: 85%
“…Falco et al (1997) derived v (light) = 279 13 km/s, and so, with the whole lens model and the time delay above mentioned, one obtains H 0 = 66 +15 14 km/s/Mpc (2 ). This estimate is 10% accurate at 1 (Oscoz et al 1997). We h o w ever remark that a new lens model satisfying the constraints from radio mapping as well as new optical constraints deduced from HST observations is now in progress (Bernstein et al 1997).…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…The Cross correlation method (Kundic et al 1997;Oscoz et al 1997), PRH method ) and Dispersion spectra (Pelt et al 1996), described in Sects. 3.1-3.3, respectively, have been widely used in the literature.…”
Section: Methods For Estimating the Time Delaymentioning
confidence: 99%